Políticas de selección y reclutamiento de personal de la Hacienda Bananera La Margarita - Baba - Hernandez Murillo, Cinthia Katiuska (2021)
The purpose of this case study is to publicize the processes of Recruitment and Selection of personnel at Hacienda Bananera La Margarita, which are considered to fill vacancies in the agricultural sector, as well as to determine if policies are used for the hiring of said vacancies. Recruitment and personnel selection policies are guidelines to follow, which are aimed at providing human resources to a company or organization at the appropriate time. The Banana Farm does not have a manual or guide to hire personnel, the day laborers are often rotated, and they do not have the experience and knowledge necessary to work in positions, such as: disinfection, packaging and loading. Finally, the administrative staff does not have a record of the people who work and have worked in the company. All the information could be obtained through an interview and surveys carried out with the workers' personnel.